Improving The Seventh Grade Students' Summarizing Skills Of The Fiction Books Using The Ok5r Method At SMP Negeri 1 Tuhemberua - Antonius - Gea (Indonesian Journal of Education and Mathematical Science, 2020)
Summarizing fiction books is a person's activity to effectively present a long discourse in a short form so that it can represent the entire content of the reading text which contains writing based only on the imagination of the author or author. Fiction books in the form of short stories (short stories, novels, soap operas, dramas, drama films, comedy films, horror films, and action films and so on. The purpose of this study was to improve students' ability to summarize fiction books using the OK5R method. To achieve this goal, the researcher uses the Classroom Action Research method with the implementation procedure are (1) planning, (2) action, (3) observation, (4) reflection. This classroom action research activity was carried out in two cycles using data collection techniques, observation sheets and assessment sheets. The subjects of this study were students of class VII-A SMP Negeri 1 Tuhemberua in the even semester, totalling 20 students with 10 boys and 10 girls. The results of this study indicate that the first cycle with the lowest value is 40 and the highest value is 90 with an average value of 64.25. Meanwhile, in the second cycle, the lowest score is 75 and the highest one is 100 with an average value of 84.75. The results of observations by researchers in the first cycle of the first meeting were 47.05% and the second meeting was 64.70%, while in the second cycle the first meeting was 76.47% and the second meeting was 94.11%. The results of student observations in the first cycle of the first meeting were 67.18% and the second meeting was 69.47%, while in the second cycle the first meeting was 89.68% and the second meeting was 97.89%. Based on the results of the study, the researchers concluded that using the OK5R method can improve students' ability to summarize fiction books (short stories) in class VII-A Tuhemberua in the 2019/2020 Learning Year. Suggestions: 1) for students of SMP Negeri 1 Tuhemberua, the results of this study can motivate students in learning Indonesian, 2) for teachers at SMP Negeri 1 Tuhemberua, the results of this study can be used as a guide in learning the material for summarizing fiction books.Keywords:Summarizes, fiction books, OK5R method